Electric field induced, superhydrophobic to superhydrophilic switching in multiwalled carbon nanotube papers - Kakade, Bhalchandra A.; Mehta, Rutvik; Durge, Apurva; Kulkarni, Sneha; Pillai, Vijayamohanan (Nano Letters, 2008)
Superhydrophobic multiwalled carbon nanotube bucky paper, fabricated after ozonolysis, shows fascinating electrowetting behavior, which could be remarkably tuned by changing key solution variables like the ionic strength, the nature of the electrolyte, and the pH of the water droplet. More significantly, the droplet behavior can be reversibly switched between superhydrophobic, Cassie-Baxter state to hydrophilic, Wenzel state by the application of an electric field, especially below a threshold value.

Near-complete phase transfer of single-wall carbon nanotubes by covalent functionalization - Kakade, Bhalchandra A.; Patil, Sanjay; Sathe, Bhaskar; Gokhale, Suresh; Pillai, Vijayamohanan (Journal of Chemical Sciences, 2008)
We describe here an efficient phase transfer of single wall carbon nanotubes (SWNTs) from aqueous to non-aqueous media using a unique amide functionalization route, where water soluble SWNTs (2.6 mg/mL) are effectively transferred to solvents like chloroform, toluene and CS(2). A maximum of 30 wt% of oxygenated groups have been generated on the side walls by rapid microwave treatment, leading to a solubility of more than 2.6 mg/mL in water. Approximate surface amine coverage of 50% has been accomplished after oxalyl chloride treatment as inferred from thermogravimetry and X-ray photoelectron spectroscopy by controlling several key parameters associated with the extent of functionalization including purity of the sample, temperature and time.
Keywords: Carbon nanotubes; microscopy; Microwave; Nanostructures; solubility of SWNTs

Design of an "allsolid-state'' supercapacitor based on phosphoric acid doped polybenzimidazole (PBI) electrolyte - Rathod, Dhanraj; Vijay, Meenu; Islam, Md. Nazrul; Kannan, Ramaiyan; Kharul, Ulhas K.; Kurungot, Sreekumar; Pillai, Vijayamohanan (Journal of Applied Electrochemistry, 2009)
The effectiveness of phosphoric acid doped polybenzimidazole as a polymer electrolyte membrane to fabricate an all solid-state super capacitor has been explored using hydrous RuO(2)/carbon composite electrodes (20 wt.%) of surface area 250 m(2) g(-1) with many intrinsic advantages. The electrochemical evaluation of these super capacitors through cyclic voltammetry, charge/discharge and impedance measurements demonstrate the utility of this type of thin, compact and flexible supercapacitor capable of functioning at 150 degrees C to yield a maximum capacitance of about 290 F g(-1) along with a life of more than 1,000 cycles. A power density of 300 W kg(-1) and energy density of 10 Wh kg(-1) have been accomplished although the equivalent series resistance (ESR) of about 3.7 Omega needs to be reduced further for high rated applications.
Keywords: Electrochemical characterization; Electrochemical supercapacitor; Energy storage device; PBI electrolyte; RuO(2)/carbon composite

Photophysical and photoconductivity properties of thiol-functionalized graphene-CdSe QD composites - Debgupta, Joyashish; Mandal, Sadananda; Kalita, Hemen; Aslam, Mohammed; Patra, Amitava; Pillai, Vijayamohanan (RSC Advances, 2014)
Graphene-semiconductor QD hybrid nanostructure materials have recently emerged as a new class of functional materials because of their potential applications in solar energy conversion, optoelectronic devices, sensing etc. Here, oleic acid-capped CdSe QDs are attached to -PhSH functionalized graphene by ligand exchange via bonding with the -SH group. The shifting of the G-band and D-band due to structural changes for the attachment of QD with graphene has been evaluated by using Raman spectroscopy. Steady state photoluminescence (PL) and time resolved fluorescence measurements have been employed to understand the electronic interactions between graphene and CdSe QDs. A time resolved fluorescence spectroscopic study has been used to understand the fluorescence dynamics of the photoexcitated CdSe QDs in the presence of graphene. It is evident that the electron transfer occurs from photoexcited QDs to graphene and the electron transfer rate is found to be 12.8 x 10(8) s(-1) for 3.8 nm CdSe QDs. Photoconductivity properties of the graphene-QD device under illumination have been examined and it is to be noted that 2-3 fold increase in the photocurrent is found in this composite device in presence of 1.5 AM solar simulated light. The enhancement of the photocurrent in this hybrid device is found to be suitable for potential applications in optoelectronic and solar cell systems.